Optimasi Jaringan Transportasi Jalan Perkotaan Dengan Pendekatan Metode Dynamic Balanced Scorecard (Studi Kasus Pengembangan Perkotaan Bsd City) - Muhammadun, Haris (Sekretariat Badan Penelitian dan Pengembangan Perhubungan, 2012)
ABSTRACTTraffic congestion is a common cities problem. 111e sihwtion happened because of the imbalanced between demand -siqrply of the roads and the amount of vehicles. Many solutions have been carried out to solve the problem but only solve partially, the solution should be integratedsystem between infrastructure network and service nehvork, together in one good system. Optimation road transportation network in cities use dynamic balanced scorecard methode, is approach be plan with concept integration management strategic theory(balanced scorecard) and technic transportation theory (4 step models : trip generation, trip distribution, modal split, traffic assignment), and supporting by dynamic programming. The goal of the research is to improve the quality and quantity of the infrastructure network and effectivity-effisiency of the service network, so achive balanced traffic at the end traffic become safty, normally, and fluently. This condition, its mind fuel consumtion low. Key performance indicator (KPI), decided by technic guidence from the transportation ministry, the public work ministry, and the other referency.Key Words : infrastructure, service network, traffic congestion, traffic modelling, dynamic programming, balanced scorecard